Upaya Guru dalam Pengembangan Kurikulum 2013 di Sekolah MAS Al-Washliyah Tembung - Fattah Nasution, Abdul; Aldi, Muhammad; Sastra, Purnama; Adawiyah , Rabiatul; Nur Khalifah, Siti (IAI Nasional Laa Roiba Bogor, 2024)
The purpose of writing this journal is to analyze the teacher's efforts in developing the 2013 curriculum at the MAS Al-Washliyah Tembung school. The method used in this research is qualitative, descriptive with library research and field interviews. Research results that can be obtained from this study, that in developing the 2013 Curriculum, it has several components, principles, principles, and forms. So it should be noted, in developing the curriculum must pay attention to the aspects and conditions of student learning at school, starting from the affective, cognitive, and psychomotor aspects of the students themselves. This can be evaluated through several assessments which are the main goal in developing the curriculum, thus, curriculum development can take place effectively, and efficiency is as expected. Keywords : Efforts, Development, Curriculum 2013